A Sugarcane Aphid "Super‐Clone" Predominates on Sorghum and Johnsongrass from Four US States. Issue 6 (13th September 2018) - Harris-Shultz, Karen R.; Brewer, Michael J.; Wadl, Phillip A.; Ni, Xinzhi; Wang, Hongliang
Abstract : The sugarcane aphid [SCA, Melanaphis sacchari (Zehntner), Hemiptera: Aphididae], is the predominant pest of US‐grown sorghum [ Sorghum bicolor (L.) Moench]. A previous study found that a single clone was prevalent on samples collected from sorghum in seven states and one territory of the United States in 2015. We sought to determine if this clone was still prevalent on sorghum grown in 2016 and if this clone is also found on Johnsongrass [ S. halepense (L.) Pers.]. Forty‐six SCA samples were collected from primarily sorghum and Johnsongrass from 10 cities in four states, and three aphid samples from different genera ( Sipha, Rhopalosiphum, and Acyrthosiphon ) were obtained. These aphid samples were genotyped with 43 SCA simple sequence repeat (SSR) markers. The predominant aphid clone found on sorghum in 2015 was again the predominant genotype in the 2016 SCA samples collected from sorghum. This same genotype was also found for the SCA samples collected from Johnsongrass in 2015 and 2016, although two samples differed at a single locus. Mixtures of this predominant genotype with three additional genotypes of SCAs were detected for three samples (excluding the control), indicating that multiple genotypes do exist in the United States but at low levels. This study provides evidence that a SCA "super‐clone" has maintained its dominance on sorghum, and it is using the perennial Johnsongrass as an alternative host.